2017
DOI: 10.1007/s12012-017-9402-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine Particulate Matter Increases Cardiac Ischemia/Reperfusion Injury via Mitochondrial Permeability Transition Pore

Abstract: Ultrafine Particulate Matter (UFP) has been associated with increased cardiovascular morbidity and mortality. However, the mechanisms that drive PM associated cardiovascular disease and dysfunction remain unclear. We examined the impact of oropharyngeal aspiration of 100 μg UFP from the Chapel Hill, NC air shed in Sprague-Dawley rats on cardiac function, arrhythmogenesis, and cardiac ischemia/reperfusion (I/R) injury using a Langendorff working heart model. We found that exposure to UFP was capable of signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“… 35 Transition metals or organic compounds may modulate mitochondria or nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase, which deteriorates their function. 36 Our results showed that PM 10 and CAI levels at 3 days before hospitalization had the greatest correlation with admission rate for severe AECOPD events. We estimate that this is due to abnormal inflammatory response and oxidative stress.…”
Section: Discussionmentioning
confidence: 51%
“… 35 Transition metals or organic compounds may modulate mitochondria or nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase, which deteriorates their function. 36 Our results showed that PM 10 and CAI levels at 3 days before hospitalization had the greatest correlation with admission rate for severe AECOPD events. We estimate that this is due to abnormal inflammatory response and oxidative stress.…”
Section: Discussionmentioning
confidence: 51%
“…Lichtveld et al (2012) reported that aged DE produced significantly lower inflammatory responses when cultured lung cells were exposed under submerged conditions where aged DE was collected on a filter followed by particle resuspension in liquid medium compared to cells exposed at the air-liquid interface (ALI), due to lack of carbonyl compounds from filter samples. Similarly, animal studies have shown that the instillation of PMs from filter samples had no effects on preischemic cardiac function in isolated Langendorff perfused hearts (Tong et al 2010, Holland et al 2017. Further, using the same irradiation chamber and ALI in vitro exposure systems, it was demonstrated that gas-phase-products increased the toxicity of the nontoxic PM, indicating that gaseous components of air pollution might be driving the adverse health effects as they partition on and off the PM (Ebersviller et al 2012).…”
Section: Discussionmentioning
confidence: 93%
“…The study of the isolated heart is used in several types of tests being extremely useful in the translational evaluation of these pharmacological tests [32,33]. According to Tong et al [34], heart retrograde perfusion models are ex vivo methods of clinical relevance for the study of myocardial infarction to evaluate function and injury.…”
Section: Discussionmentioning
confidence: 99%